Variability in Sclerotium rolfsii associated with collar rot of sunflower - N. NARESH and S.CHANDER RAO, M. SANTHA LAKSHMI PRASAD*, K. SUJATHA, (Indian Phytopathology, 2012)
Isolates of Sclerotium rolfsii were collected from infected samples of sunflower from various sunflower growing areas of India. The isolates were studied for morphological and cultural characters, vegetative compatibility and pathogenic variability. Variations were observed in colony morphology, mycelial growth, sclerotium formation, sclerotial size, colour and number of sclerotia. The number of sclerotia in different isolates varied from 57 (Sr 3) to 306 (Sr 11). Eighty four combinations showed compatible reaction out of 231 pairings in mycelial compatibility studies. Pathogenic variability of isolates with different sunflower cultivars was carried out by soil infestation method. Based on pathogenicity, S. rolfsii isolates were divided into four groups. DRSH 1 showed resistant to moderately resistant reaction to most of the isolates, while Morden variety was susceptible to all isolates.